Melihat Kembali Potret Pendidikan di Indonesia - Khusnan Iskandar (Journal of Education and Religious Studies, 2022)
This article is a conceptual study that aims to determine the condition of education in Indonesia. The analysis used is content analysis by combining various theories studied. Education has an important role in the development of a country, including in Indonesia. This article revisits the portrait of education in Indonesia by identifying the changes and challenges faced. Through an analysis of historical and contextual approaches, this article discusses the efforts that have been made to improve accessibility, quality, and equity in education in the country. In the portrait of education in Indonesia, there are gaps between urban and rural areas, challenges related to the quality of education, curriculum, teaching methods, and gender gap issues. In addition, this article illustrates the development of higher education and the importance of the role of the government, society, and other stakeholders in improving the portrait of education in Indonesia. By looking back at this portrait of education, it is hoped that it can create better and equitable education in Indonesia, contribute to sustainable development and improve the welfare of society as a whole.